The Role of the Community Environment in Improving the Quality of Early Childhood Education at Ra Hajjah Zahara - Kharida Shaleha; Khairatunnisa; Desta Marnatal Riang Zebua (Outline Publisher, 2023)
Education from an early age for early childhood is quite important and will determine their future. One of the efforts to achieve these educational goals is to organize formal, non-formal and pre-school education that can be reached by various levels of society. Seeing this, the role of all levels of society is needed, including the government, the community and especially the family environment. The family has a very important role because the family is the main foundation of the child. Therefore educational institutions must also know and implement and strive to increase community participation to jointly bear education. With this, it is hoped that the community will increasingly compete to improve the quality of their education to a higher level.